Wsparcie finansowe w światowym rolnictwie - doświadczenia krajów OECD dziesięć lat po Rundzie Urugwajskiej GATT/WTO - Poczta, Agnieszka (Domestic Support in Agriculture - Experiences of OECD Countries 10 Years after Uruguay Round GATT/WTO, 2005)
The aim of this article is to analyze the level of domestic support in OECD countries and how it has been developing since the introduction of Uruguay Round Agreement on Agriculture. Firstly, the main decisions of URAA have been presented, but special attention has been focused on these concerning domestic support. The main survey has been conducted with the use of PSE, TSE and AMS indices. The conclusion is that domestic support in OECD countries 10 years after URAA is more or less at the same level as it was in the day URAA was signed. However, there are some important developments as far as the measures of support are concerned.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 209-215